Nutritional interventions for COVID-19: A role for Carnosine? - Feehan, J.; de Courten, M.; Apostolopoulos, V.; de Courten, B. (Nutrients, 2021)
As COVID-19 continues to take an enormous toll on global health, the effort to find effective preventive and treatment strategies has been unparalleled in recent history [1]. While the rapid rollout of vaccines is heartening, limited supply, logistical hurdles, enormous demand, and the rise of new variants of the virus will make population-scale vaccination a challenging target to meet, particularly in lower socioeconomic areas of the world [2]. This makes cheap, safe, and effective measures to limit the impact of COVID-19 of vital importance, and in this, nutritional interventions are particularly attractive as they are readily scalable. While some nutrients have garnered widespread attention for their potential use in preventing or managing COVID-19, such as vitamins B, C, and D [3,4], there are many others with powerful health-promoting effects that may have clinical utility. Carnosine is one such nutritional supplement, which could protect against some of the detrimental effects of SARS-CoV-2 infection. Carnosine is an over-the-counter nutritional supplement with a wide array of beneficial physiological effects in vivo [5,6]. Carnosine is synthesized from beta-alanine and histidine and is concentrated particularly in muscle, cardiac, and brain tissues. Carnosine is often regarded as a geroprotector, offering a range of benefits thought to improve age-related chronic diseases, longevity, and "health-span". Supplementation with carnosine is common in athletes, due to its performance-enhancing properties. However, it is cheaper to use ß-alanine, which is also the rate-limiting factor in carnosine synthesis [7]. Importantly, carnosine has strong anti-inflammatory, antioxidant, and anti-glycating effects, all important factors in the initiation and progression of many chronic conditions associated with advanced age, including diabetes and its complications, cardiovascular disease, and neurodegenerative diseases [8]. While anti-inflammatory, anti-oxidative, and anti-glycating effects make carnosine a worthy target for COVID-19 (Figure 1), more recently, carnosine has also been shown to have anti-viral properties [9,10,11,12]. The flaviviruses Zika virus and dengue virus have re-emerged, causing significant outbreaks. Although the pathophysiology of these viruses is understood, no vaccines or anti-viral drugs have been approved. Through in silico studies, it was noted that carnosine could interact with viral proteins, and in in vitro studies carnosine was able to inhibit dengue virus and Zika virus infection and replication in human liver cells [12]. The ability of carnosine to decrease nitric oxide and neutrophil influx into the upper respiratory tract has been noted to be important in controlling the initial stages of influenza A infection [10,11]. In mice, carnosine decreases mortality and pathological lung changes following infection with H9N2 swine influenza virus [9]. Due to all of these benefits, carnosine could also have a role in protecting patients against COVID-19.